The Contributions Of The Travancore Royal Family To Kerala’s Educational Development (Journal of Namibian Studies : History Politics Culture, 2022)
This paper examines the transformative educational policies and initiatives introduced by the Travancore royal family from the early 19th century to the early 20th century. By analysing reforms implemented by Rani Gouri Parvathi Bayi, Maharaja Swathi Thirunal Rama Varma, Maharaja Marthanda Varma, Maharaja Ayilyam Thirunal Rama Varma, Maharaja Moolam Thirunal Rama Varma, Rani Setu Lakshmi Bayi, and Maharaja Sree Chithira Thirunal Rama Varma, the study elucidates how a blend of traditional knowledge and modern educational practices laid a robust foundation for Kerala’s high literacy rates and social inclusivity. The paper discusses the historical context, specific policy implementations, and the lasting impact these reforms have had on the state’s educational landscape.